Multi-scale analysis of functional plankton diversity in floodplain wetlands: Effects of river regulation - Chaparro, Griselda Noemí (2019)
Riverine floodplains are among the most diverse and dynamic ecosystems, but river regulation measures have altered the natural hydrological regime threatening their ecological integrity. We compared spatial patterns of phyto- and zooplankton functional diversity and of environmental heterogeneity between floodplain wetlands located in free-flowing and impounded stretches of the Danube River (Austria). We included two nested spatial scales (different habitats and water sections within wetland areas) and two contrasting hydrological conditions (post-flood, no flood). Environmental heterogeneity was lower in the wetland in the impounded stretch than in the free-flowing ones. At post-flood conditions, increased alpha diversity of rotifers and microcrustaceans and decreased beta diversity of phytoplankton and rotifers occurred in the impounded stretch as compared to the wetlands in free-flowing one. Beta diversity was higher between water sections than between habitats in free-flowing wetlands and similar across scales in the wetland in the impounded stretch. Regarding functional composition, the wetland in the impounded stretch hosted more homogeneous communities, as some ecological traits were nearly absent. Our results indicate that patterns of functional diversity in floodplain wetlands affected by river regulation are altered, highlighting the major role of the gradient of lateral connectivity and dynamic water level fluctuations as drivers for planktic diversity in river floodplains. This study contributes with essential knowledge to optimize restoration and diversity conservation measures in riverine ecosystems.